English-Bulgarian translation of legal vocabulary from the semantic field of property - Dimitrova, Irina (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The paper presents some specifics of the English- Bulgarian translation of terminology from the semantic field of ownership discussing the challenges before the legal translator. The semantic field is limited to the terms concerning freehold property rights with no claim for an exhaustive analysis or inclusion of all field terms. The outlines of the field are fuzzy due to the polysemy characterizing the terms whose meanings are identifiable both in the field of freehold property rights and in neighboring fields such as the field of possession, for example, which as a concept is also an element of leasehold property rights. The degree of control exercised by the owner serves as a distinguishing criterion between the terms belonging to the semantic field of ownership and those of its elements. At the lexical level, on the other hand, this “distinction” manifests itself depending on the connotative connections that a given term establishes with other elements of the text and context. The ambiguity of concepts in a close context, combined with cultural and legal system differences between the two languages, as well as the imperative need for semantic and intercultural precision, form the complex nature of the challenges facing the translator of a legal text.